Pengaruh Financial Literacy, Financial Technology dan Lifestyle terhadap Perilaku Keuangan - Juwita Nur Natasha; Achmad Hasan Hafidzi; Wahyu Eko Setianingsih (Universitas Nusantara PGRI Kediri, 2025)
Finance plays an important role in supporting company growth. Without good financial management, companies can face various obstacles that risk thwarting the achievement of business goals. This study is intended to explore and analyze the extent to which financial literacy, utilization of financial technology, and lifestyle patterns influence financial management behavior among students domiciled in Jember Regency. In its implementation, this study applies a quantitative method involving 400 respondents as a sample. Sample selection was carried out using the Non-Probability Sampling method with a purposive sampling approach. Data collection was obtained through the distribution of questionnaires. Data analysis techniques used include testing research instruments, classical assumption tests, multiple linear regression analysis, hypothesis testing, and calculating the coefficient of determination. Based on the results of the analysis, it is known that financial literacy, utilization of financial technology, and lifestyle have a significant effect on the financial behavior of students in Jember Regency.